Too Young to Die: Regression Discontinuity of a Two-Part Minimum Legal Drinking Age Policy and the Causal Effect of Alcohol on Health - Gawain Heckley; Ulf-G. Gerdtham; Johan Jarl (Lund University, School of Economics and Management, Department of Economics, 2018)
This study examines the impact of Sweden's unique two-part Minimum Legal Drinking Age (MLDA) policy on alcohol consumption and health using regression discontinuity design. In Sweden on-licence purchasing of alcohol is legalised at 18 and off-licence purchasing is legalised later at 20 years of age. We find an immediate and significant 6% jump in participation and a larger increase in number of days drinking at age 18 of about 16% but no large jumps at age 20. No discernible increases in mortality at age 18 or 20 are found but hospital visits due to external causes do see an increase at both 18 and 20 years. Compared to previous findings for single MLDAs the alcohol impacts we find are smaller and the health impacts less severe. The findings suggest that a two-part MLDA can help young adults in their transition to unrestricted alcohol and help contain the negative health impacts that have been observed elsewhere.
Keywords: I12; I18; 330; Alcohol consumption; regression discontinuity; minimum legal drinking age